Conceptual foundations for the formation of economically feasible costs in railway transport enterprises - Bohomolova, Nadiia; Ovrutska, Vitalina (Technium Social Sciences Journal, 2020)
The article deals with the need to improve the cost management system of the railway transport of Ukraine in current economic conditions. Diagnostics of the cost management system demonstrated that modern methods of cost optimization have not been fully used so far. Optimization is often considered as the reduction in the resource use; therefore, due to price increase of materials and other resources, it frequently leads to negative consequences. In addition, the cost management system itself and its diagnostic tools are aimed at analyzing the past, but not shaping future development, which reduces the efficiency of financial management. The article outlines a system of principles for the formation of economically feasible costs, including the requirements of two blocks. The first block is aimed at increasing the efficiency of the cost management system as an integral part of the enterprise management system. The second one is aimed at ensuring the practice of transparency and open interaction with key stakeholders. The authors substantiate the organizational and economic approach to the implementation of segment-oriented cost management. This approach is based on (1) regulatory framework in terms of composition and specification of the costs that are not taken into account in the regulation of price and tariffs; (2) ensuring the procedures for compliance of the nomenclature of income and expenses); (3) use of systemic and situational cost management tools for adaptation and enhancing of competition policy and reforms implementation. Cost management of various segments (freight, passenger transportation, ancillary activities, etc.) requires different management forms and techniques. The provisions of the suggested conceptual approach to cost management of railway enterprises should be implemented in close accordance with two key factors - (1) the strategic principles of the railway enterprise development and (2) its revenue management system